Immune changes at the injured sites in oxazolone-induced ulcerous colitis: Influence of ozone therapy - E. V. Davydova (Medicinskaâ Immunologiâ, 2022)
Impaired immunoregulation and development of autoimmune response to antigens of own intestinal microbiota and inflammation-altered antigens of colonic cells represent the key links in pathogenesis of inflammatory bowel diseases. Multimodal biological effects of ozone presunme the usage of local and systemic ozone therapy in complex treatment of many inflammatory diseases of the gastrointestinal tract. The aim of our work was to study effects of intraperitoneal and rectal ozone therapy upon immune parameters of the lesion focus in oxazolone-induced ulcerative colitis in the course of time. The study was carried out on 64 adult male inbred Wistar rats weighing 240±20 g. Experimental ulcerative colitis was produced by oxazolone treatment (4-ethoxymethylene-2-phenyl-2-oxazolin-5-one) (SigmaAldrich, USA). The ozone-oxygen mixture was injected intraperitoneally or rectally at a concentration of 1.0-1.2 mg/l, once a day, in a volume of 10 ml, at the 6-day course. The results of experiments were recorded on the days +2, +4 and +6. The concentrations of IL-17 and IL-23 was determined in a homogenate of intestinal tissues (Bender Medsystems, Austria) using a Personal LAB analyzer; expression of CD4 and FoxP3 on intestinal lymphocytes was determined by immunohistochemistry technique (ElisaKit, China). The observed tissue damage of large intestine showed an increase from day 2 to day 6 of oxazolone-induced ulcerative colitis. The total number of lymphocytes significantly increased upon development of experimental colitis, with parallel decrease in the number of CD4+ lymphocytes and FoxP3-positive T lymphocytes. IL-17 and IL-23 concentrations in the tissues increased with the severity of inflammatory changes in the lesion focus. Intraperitoneal ozone administration was associated with significant reduction of lymphocyte contents in the damaged tissues on the 6th day, whereas the numbers of CD4+ and FoxP3 positive T lymphocytes normalized by the 6th day. The levels of IL-17 and IL-23 increased from day 2 to day 6, with a lower IL-23 values on day 6 as compared with non-treated animals. Rectal administration of ACS led to the normalization of FoxP3 cells on the 6th day to the values of intact animals. The levels of proinflammatory cytokines (IL-17 and IL-23) significantly decreased on the 6th day as compared to the group of animals without treatment, which could be due to anti-inflammatory properties of ozone.